Jakub VI (I) Stuart w angielskiej przestrzeni religijnej - Basista, Jakub (Studia Europaea Gnesnensia, 2018)
The paper is concerned with the religious issues in England at the time when James VI Stuart, King of Scotland, ascended to the throne. The reign of the land dominated by the Anglican confession, with the king as the supreme head of the Church, going into the hands of a ruler who had grown up in a Presbyterian environment posed number of questions and challenges before the monarch and his subjects as well.